THE INFLUENCE OF BRAND IMAGE, ONLINE CUSTOMER REVIEWS AND PRICE PERCEPTIONS ON THE ORIGINOTE HYALUCERA MOISTURIZER PURCHASE DECISION - Rinda Pramudya Pangesti; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research aims to determine the influence of Brand Image, Online Customer Review and Price Peceptions on The Originote Hyalucera Moisturizer Purchase Decision. Case study Gen Z Simo Pomahan Baru Barat Surabaya. The method used in this research is a quantitative method using the lemeshow rormula on 100 respondents. This research uses the SPSS data analysis method to analyze multiple linear regression, F test an t test. Brand image has a significant influence on purchasing decision, Online Customer Rewiew do not have a significant influence on purchasing deisions and Price Perception has a significant influence on purchasing decisions